2001
DOI: 10.1128/aac.45.11.3132-3139.2001
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activities and Cytotoxicity Studies of Six New Azasordarins

Abstract: GW 471552, GW 471558, GW 479821, GW 515716, GW 570009, and GW 587270 are members of a new family of sordarin derivatives called azasordarins. The in vitro activities of these compounds were evaluated against clinical isolates of yeasts, including Candida albicans, Candida non-albicans, and Cryptococcus neoformans strains. Activities against Pneumocystis carinii, Aspergillus spp., less common molds, and dermatophytes were also investigated. Azasordarin derivatives displayed significant activities against the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
38
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 19 publications
2
38
0
Order By: Relevance
“…On the other hand, R-135853 exhibited weak or no activity against C. parapsilosis, C. krusei, and Aspergillus spp. These in vitro characteristics of R-135853 are similar to those of other sordarins reported previously (16,17). It is remarkable that R-135853 exhibited potent activities against C. albicans, whether or not the strains showed resistance to FLC.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…On the other hand, R-135853 exhibited weak or no activity against C. parapsilosis, C. krusei, and Aspergillus spp. These in vitro characteristics of R-135853 are similar to those of other sordarins reported previously (16,17). It is remarkable that R-135853 exhibited potent activities against C. albicans, whether or not the strains showed resistance to FLC.…”
Section: Discussionsupporting
confidence: 74%
“…This multiple interaction may explain the high degree of selectivity of this class of compounds between fungal and mammalian cells (12). Some pharmaceutical companies have reported that sordarin derivatives exhibit potent antifungal activities with relatively broad-spectrum activities in vitro and that some compounds exhibit good efficacies in vivo (2,7,15,16,17,25,26). We also synthesized sordarin derivatives from zofimarin, a sordarin-related natural product which was isolated from the fungus Zopfiella marina (32).…”
mentioning
confidence: 99%
“…Their spectrum includes most fungal pathogens that affect immunocompromised patients, i.e. Candida spp., Cryptococcus neoformans, Pneumocystis carinii, and several endemic American fungi as well as dermatophytes (2). These compounds exert their antifungal activity by selectively inhibiting the elongation step of protein synthesis in the target organisms, but not in higher eukaryotes (3).…”
mentioning
confidence: 99%
“…In addition, the low toxicity of GW471552 and GW471558 has been demonstrated in vitro (13) and confirmed by preliminary mouse toxicity tests [E. Herreros, A. Martínez, M. J. Almela, E. Jiménez, S. Lozano, M. J. Pérez, and D. GargalloViola, Abstr. 40th Intersci.…”
mentioning
confidence: 99%
“…A further evolution of this class of compounds has led to a new family of substances, azasordarins, that have a similar biological profile but easier chemical synthesis. Azasordarins have demonstrated excellent in vitro activity against key fungal pathogens, including P. carinii (13), and therapeutic efficacy in experimental rodents of oral and vulvovaginal candidiasis (21).…”
mentioning
confidence: 99%